UNVEILING BALI'S HIDDEN FACET: The Narrative Identity of the Pegayaman Village Muslim Community in Buleleng (JOURNAL OF INDONESIAN ISLAM, 2024)
This article examines the narrative identity of the Muslim community in Pegayaman Village, located in Sukasada District, Buleleng Regency, Bali Province. As the oldest Muslim community on the predominantly Hindu island of Bali, the people of Pegayaman Village possess unique characteristics compared to other Muslim communities on the island. These include the tradition of combining Balinese and Arabic names for their descendants, the use of Arabic books translated into Balinese in daily life, and various forms of acculturation between Balinese traditions and Islamic teachings. These unique features suggest a dual identity for the Pegayaman community, representing themselves as both Balinese and Muslim. The theoretical framework for this study is Paul Ricoeur's narrative identity theory, while the research approach employs a qualitative method using narrative analysis and literature review. The findings indicate that both historical and fictional narratives contribute to the formation of the Pegayaman community's narrative identity. Meanwhile, the idem and ipse identities, reflected in the culture, traditions, and character of the Pegayaman community, are rooted in both extralinguistic and linguistic dimensions. Moreover, the narrative identity of the Pegayaman community generates ethical, aesthetic, and political implications for its members.